PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN (SAP), PENGENDALIAN INTERN AKUNTANSI, DAN PENGAWASAN KEUANGAN TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH - Dewa Ayu Sri Ganitri; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of the understanding of government accounting standards (SAP), internal accounting controls and financial control on the value of local government financial reporting information on the SKPD of Denpasar City. This study uses a quantitative approach using primary data through a questionnaire. The sampling technique was using purposive sampling method. Respondents in this study are employees who carry out accounting / financial administration functions at 36 SKPD of Denpasar City. The number of samples used was 108 respondents. The data obtained were then analyzed using SPSS 21. The results showed that the understanding of Government Accounting Standards (SAP) had a positive and significant effect on the value of local government financial reporting information. Accounting internal control has no significant effect on the value of local government financial reporting information and financial supervision has a positive and significant effect on the value of local government financial reporting information in the SKPD of Denpasar City.